2021
DOI: 10.3390/cancers13235979
|View full text |Cite
|
Sign up to set email alerts
|

MiR-195 and Its Target SEMA6D Regulate Chemoresponse in Breast Cancer

Abstract: Background: poor prognosis primary breast cancers are typically treated with cytotoxic chemotherapy. However, recurrences remain relatively common even after this aggressive therapy. Comparison of matched tumours pre- and post-chemotherapy can allow identification of molecular characteristics of therapy resistance and thereby potentially aid discovery of novel predictive markers or targets for chemosensitisation. Through this comparison, we aimed to identify microRNAs associated with chemoresistance, define mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…Furthermore, SEMA6D levels may be closely correlated with esophageal cancer and lung adenocarcinoma [ 24 , 25 ] and can regulate angiogenesis in colorectal cancer [26] . It has also been reported that SEMA6D could regulate chemoresponse in breast cancer [27] . Here, the results of the univariate analysis showed that OS was more affected by SEMA6D than DFS.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, SEMA6D levels may be closely correlated with esophageal cancer and lung adenocarcinoma [ 24 , 25 ] and can regulate angiogenesis in colorectal cancer [26] . It has also been reported that SEMA6D could regulate chemoresponse in breast cancer [27] . Here, the results of the univariate analysis showed that OS was more affected by SEMA6D than DFS.…”
Section: Discussionmentioning
confidence: 88%
“…It must be noted that in addition to their role in predicting the outcome of breast cancer, miRNAs are also known to predict response to chemotherapy (chemoresistance). One example is miRNA-195 which was found to induce resistance to chemotherapy in breast cancer by reducing the levels of a protein known as SEMA6D [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…How to overcome resistance to chemotherapy, particularly in indications such as TNBC, is a major challenge. Recently, some biological mechanisms have been described, such as the presence of liver X receptor alpha [ 49 ] or SEMA6D/miRNA 195 in triple-negative tumours [ 50 ]. In this context, the proposed combination described in this article could target those mechanisms, improving the efficacy of current therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%